Cardiovascular Disease Attributable to High Systolic Blood Pressure in Younger Adults Requires Greater Attention: Insights from the Global Burden of Disease Study 2021 - Fanqi Li; Jiasong Li; Siyuan Tan; Gaoming Zeng; Jiayi Zhu; Jiabao Zhou; Zixi Zhang; Qiuzhen Lin; Na Liu; Qiming Liu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Cardiovascular disease (CVD) represents the most significant global burden among all diseases. High systolic blood pressure (HBP) is the most prevalent risk factor for CVD. This study aims to investigate the global burden of CVDs attributable to high systolic blood pressure (HBP‐CVD) and to assess the effectiveness of disease control across different age groups. Methods The burden was assessed by analyzing the numbers, age‐standardized rates of deaths, and disability‐adjusted life‐years, alongside the corresponding estimated annual percentage change, stratified by age, sex, sociodemographic index, and geographical regions. Results From 1990 to 2021, the age‐standardized rates of death and disability‐adjusted life‐years declined, with estimated annual percentage changes of −1.45 and −1.36, respectively. However, owing to the growth in population, the current burden of HBP‐CVD is increasing. The age‐period‐cohort model suggests that the alleviation of disease burden is more pronounced in populations ≥50 years of age, with the lowest point occurring around 70 years of age. The age‐stratified estimated annual percentage change further substantiates this issue, revealing that disease control efforts are least effective in the 15 to 49 years of age group, compared with the 50 to 69 and 70+ years of age groups. Overall, health inequities in HBP‐CVD are decreasing, yet they persist. More importantly, health inequities in the 15 to 49 years of age group have exacerbated from 1990 to 2021. Conclusions The burden of HBP‐CVD remains severe, and disease control was least effective in the 15 to 49 years of age group compared with the 50 to 69 and 70+ years of age groups. Urgent adjustments to health care policies are imperative.